Internationalizing the student experience through computing for social good - Aheer, Komal; Bauer, Ken; Macdonell, Cam (My University, 2020)
Information technology has connected our world and its citizens in incredible ways. Despite this connectedness, students are often isolated within the "online bubbles" of their own university, city, or country. Technology provides a great opportunity to connect them to a broader global experience. We have developed and piloted a cross-institution activity as part of an Internationalization at Home (IaH) initiative to expose first year computer science students to the concept of computing for social good in an international context. We explore how differences in culture can influence students' perceptions and approaches to computing for social good. Specifically, we had students from a Mexican and a Canadian university explore how computing for social good could be used to solve issues they faced in their communities. Students participated in surveys to propose and then rank applications for social good. The students also participated in a videoconference discussion with the students from the other school to discuss their choices. Thematic analysis revealed that the students had much more in common with each other than they had differences. Both groups not only focused on similar areas of interest, but they also tended to focus on solving issues with a local scope rather than national or global scope. Despite their cultural differences, the majority students felt they were more similar to their peers of the other culture than they were different.
Keywords: social good; internationalization; education; society